2002
DOI: 10.1007/s00217-002-0548-4
|View full text |Cite
|
Sign up to set email alerts
|

Analytical methods for the determination of the geographic origin of Emmentaler cheese. Main framework of the project; chemical, biochemical, microbiological, colour and sensory analyses

Abstract: Emmentaler is a hard cheese produced and consumed in many countries. The authenticity of this cheese variety is becoming a matter of national importance with the imminent opening of the cheese market in Switzerland and the introduction of the PDO label for the Emmentaler Switzerland™. This paper is the first in a series reporting the search for parameters that make possible a geographic discrimination of Emmentalers. Twenty Emmentaler cheese samples from six regions in Europe (one from Switzerland, two from Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In the beginning, the tested samples exhibited an average value of 10.77, which increased until reaching an average value of 19.03, at the 80 d of ripening. These results agree with those of other authors such as Lee et al [48], Pinho et al [46], Pillonel et al [52], and Rohm and Jaros [53]. However, Tarakci et al [45] and Juric et al [48] reported a decrease in b* value during ripening in herby pickled cheese and semi-hard cheeses, respectively.…”
Section: Color In Manchego-style Cheesessupporting
confidence: 91%
“…In the beginning, the tested samples exhibited an average value of 10.77, which increased until reaching an average value of 19.03, at the 80 d of ripening. These results agree with those of other authors such as Lee et al [48], Pinho et al [46], Pillonel et al [52], and Rohm and Jaros [53]. However, Tarakci et al [45] and Juric et al [48] reported a decrease in b* value during ripening in herby pickled cheese and semi-hard cheeses, respectively.…”
Section: Color In Manchego-style Cheesessupporting
confidence: 91%